2002
DOI: 10.1109/tcomm.2002.1006562
|View full text |Cite
|
Sign up to set email alerts
|

On the systematic measurement errors of correlative mobile radio channel sounders

Abstract: We show that measurements of time-varying mobile radio channels obtained with uncalibrated correlative channel sounders are affected by four different types of systematic errors (commutation, pulse-compression, aliasing, and misinterpretation error). We analyze these errors and provide upper error bounds that are formulated in terms of channel and sounder parameters. Based on these error bounds, we provide guidelines for a judicious choice of important sounder parameters. Computer simulations using a simple tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
(62 reference statements)
1
31
0
1
Order By: Relevance
“…However, an important difference from conventional spectral estimation is that realizations of the process can only be obtained by means of a channel sounding procedure that generally introduces a systematic error (bias) [26]. Our SF estimation methods are also based on channel sounding but in such a way that the corresponding bias can be compensated.…”
Section: Channel Soundingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an important difference from conventional spectral estimation is that realizations of the process can only be obtained by means of a channel sounding procedure that generally introduces a systematic error (bias) [26]. Our SF estimation methods are also based on channel sounding but in such a way that the corresponding bias can be compensated.…”
Section: Channel Soundingmentioning
confidence: 99%
“…Including measurement noise , i.e., 2 , the output of the receive filter is (10) where is the filtered noise. If the product of maximum Doppler shift and receive filter length satisfies , it can be shown that the LTV channel filter and the receive filter approximately commute, i.e., we can consider the receive filter to be moved to the transmitter side [26]. Thus, for with the "virtual sounding signal" (11) Inserting this approximation into (10), the output of the receive filter becomes (12) In view of Section III-A, and must be chosen such that (pulse compression), i.e., is approximately an impulse train.…”
Section: B Correlative Channel Soundingmentioning
confidence: 99%
“…For linear time-varying SISO physical channels, an analysis of the systematic measurement errors incurred by correlative channel sounders (due to the time-varying nature of the physical channel) is reported in [1]. Models for the phase noise power spectral density (PSD) of a 5 GHz and a 50 GHz frequency synthesizer as well as an expression for the phase-noise induced reduction of the dynamic range of m-sequences can be found in [4].…”
Section: Previous Related Workmentioning
confidence: 99%
“…In the literature, the term correlation sounder is usually reserved for a more specific setup where r(t) = s * (−t) with s(t) resulting from a BPSK modulated pseudo-(random) noise sequence (PNS) (typically an m-sequence). The widely used class of channel sounders employing chirp or multisine sounding sequences [1], [16]- [19] satisfies the conditions stated in the previous paragraph and hence fits into our framework.…”
Section: ) Correlation-based Soundingmentioning
confidence: 99%
See 1 more Smart Citation